Evaluation of the implant-bone interface integration using PRGF in the dog jaw - Ali Rafidargahi; Reza Birang; Mohammad Tavakoli; Ali Rafie Dargahi; Ali Reza Torabi (Isfahan University of Medical Sciences, 2011)
Introduction: It has been demonstrated that use of plasma rich in growth factors produces a dynamic surface on the implants, which accelerates the healing process. This study undertook a histologic and histomorphometric evaluation of the effect of platelet-rich growth factors (PRGF) on the amount of bone regeneration around dental implants.Materials and Methods: In this animal-intervention study, two systemically healthy Persian mix-breed dogs were selected. Three months after extraction of the dogs' mandibular premolars on both sides, 12 implants were selected from the OIC system with a length of 10 mm and a diameter of 5 mm. Six implants were placed in the osteotomy cavities using growth factors and 6 others were placed in the osteotomy cavities without PRGF. After 12 weeks, all the implants were removed along with the surrounding bone using Trephine bur. The samples were evaluated under a light microscope subsequent to sectioning. Data were analyzed with t-test and Mann-Whitney test (α = 0.05).Results: The results of the present study indicated that histologically, there was a significant increase in the amount of regenerated bone around the implants; moreover, thickness and maturity of bony trabeculae were not different in the samples containing PRGF in comparison with the control samples.Conclusion: According to the results, implant-bone interface integration rate around dental implants coated with PRGF was higher compared to the control group Key words: Animal study, Dental implants, Growth factor, Histomorphometry, Histology, Plasma.